A cross-sectional study of factors influencing sexual health among spouses of patients with cervical cancer - Yan Shi; Li Zhang; Yu Zhou; Xuejun Liao; Tingting Zhu; Jun Cai (PLoS ONE, 2025)
Background After treatment, cervical cancer patients commonly experience sexual health problems that lead to marital conflict. However, the sexual health cognition, distress and needs of patients’ spouses remain unclear. This study examined the factors influencing sexual health among spouses of patients with cervical cancer and provided a reference for targeted nursing interventions. Methods This cross-sectional study was conducted in Chongqing, China. A total of 202 spouses of patients with cervical cancer were selected via convenience sampling. All participants completed the questionnaire via WeChat from September 27 to October 5, 2022. The questionnaire assessed demographic information, clinical information, and information about sexual health cognition, sexual distress and sexual needs. Multiple linear regression analysis was used to identify the factors associated with sexual health cognition. Pearson’s correlation analysis was used to analyse the correlations among sexual cognition, distress and needs. Results The cognitive scores of the spouses of cervical cancer patients with respect to sexual health ranged from 6 to 25 (13.79 ± 6.74). The distress scores ranged from 8 to 35 (27.24 ± 7.88). The need scores ranged from 3 to 12 (8.68 ± 3.64). Age, education level, place of residence and other factors affected sexual health cognition. Age (β, -0.178; 95% CI, 0.099–1.060), education level (β, 0.152; 95% CI, 0.021–0.663), place of residence (β, 0.665; 95% CI, 0.102–5.789), occupation type (β, 0.507; 95% CI, 0.485–4.982), and monthly family income (β, 0.229; 95% CI, 0.311–1.344) were associated with higher levels of sexual health cognition. The results of Pearson’s correlation analysis revealed that there was a negative correlation between sexual health cognition and distress (r = - 0.6165, 95% CI: -0.69 to -0.52, P < 0.001), that cognition was positively correlated with needs (r = 0.6757,95% CI 95% CI: 0.59 to 0.74, P < 0.001), and that distress was positively correlated with needs (r = 0.6860, 95% CI: 0.60 to 0.75, P < 0.001). Conclusions Our study revealed that sexual health cognition among spouses of patients with cervical cancer is affected by multiple factors. The degree of sexual distress among these individuals is high. There was a negative correlation between sexual cognition and distress, a positive correlation between sexual cognition and demand, and a positive correlation between sexual distress and demand. These results suggest that nurses should also include the patient’s spouse in the care process and provide targeted sexual health guidance, thereby improving the overall quality of life of patients and spouses.